Orazio und Artemisia Gentileschi father and daughter painters in Baroque Italy - Rosen, Valeska von 1968- (2002)
Rezension zu: Orazio and Artemisia Gentileschi. Father and Daughter Painters in Baroque Italy, Rom, Museo del Palazzo di Venezia, 15.10.2001-6.1.2002; New York, The Metropolitan Museum of Art, 14.2.-12.5.2002; Saint Louis, Art Museum, 15.6.-15.9.2002
Elektronische Reproduktion der Druckausgabe